Diagnostic Properties of Total and Free Prostate-Specific Antigen to Predict Overall and Clinically Significant Prostate Cancer Among Men With Low Testosterone and Prior Negative Biopsy - Schwarzman, Logan S.; Pagani, Rodrigo L.; Ohlander, Samuel J.; Mima, Mahmoud; Abern, Michael R.; Andriole, Gerald L.; Freedland, Stephen J.; Moreira, Daniel M. (Urology (Ridgewood, N.J.), 2020)
To evaluate whether total serum PSA, free-PSA ratio and PSA density have similar diagnostic properties for detecting prostate cancer (PCa) and clinically-significant (cs) PCa in men with normal testosterone compared to men with low testosterone with a prior negative biopsy. We conducted a retrospective analysis of 3295 men undergoing a 2-year prostate biopsy following a negative prestudy biopsy in the placebo arm of the Reduction by Dutasteride of PCa Events (REDUCE) study. Men were divided in 2 groups based on testosterone level < or ≥300 ng/dL. Diagnostic properties of total serum PSA, free-PSA ratio, and PSA density to predict PCa and csPCa, defined as Gleason score ≥7, were determined for several thresholds and plotted as receiver operator characteristic curves. A total of 603 men (18.3%) had low testosterone. The prevalence of PCa and csPCa was 92 (15.3%) and 27 (4.5%), respectively, for low testosterone men compared to 458 (17.0%) and 138 (5.1%), correspondingly, for normal testosterone men. Total PSA, free-PSA ratio and PSA density showed similar sensitivity, specificity, and accuracy to predict PCa and csPCa among low testosterone men compared to normal testosterone men. Among subjects in a clinical trial with a prior negative biopsy, total PSA, free-PSA ratio and PSA density have comparable diagnostic characteristics for PCa screening in low and normal testosterone men.